Cross-Comparison of 4-Dimensional Flow Magnetic Resonance Imaging and Intraoperative Middle Cerebral Artery Pressure Measurements Before and After Superficial Temporal Artery-Middle Cerebral Artery Bypass Surgery. Issue 5 (30th August 2021) - Sekine, Tetsuro; Murai, Yasuo; Orita, Erika; Ando, Takahiro; Takagi, Ryo; Amano, Yasuo; Matano, Fumihiro; Iwata, Kotomi; Ogawa, Masashi; Obara, Makoto; Kumita, Shinichiro
Abstract: BACKGROUND: The hemodynamic changes after superficial temporal artery (STA) to middle cerebral artery (MCA) bypass surgery are unclear. OBJECTIVE: To clarify the hemodynamics by comparing flow parameters obtained by 4-dimensional (4D) flow magnetic resonance imaging (MRI) and intraoperative MCA pressure measurement. METHODS: We recruited 23 patients who underwent STA-MCA bypass surgery for internal carotid artery (ICA) or MCA stenosis. We monitored intraoperative MCA, STA, and radial artery (RA) pressure. All patients underwent 4D flow MRI preoperatively and 3 wk after surgery to quantify the blood flow volume (BFV) of the ipsilateral ICA (BFViICA ), contralateral ICA (BFVcICA ), basilar artery (BFVBA ), ipsilateral STA (BFViSTA ), and contralateral STA (BFVcSTA ). The sum of intracranial BFV was defined as BFVtotal . We compared BFV parameters and intraoperative pressure. RESULTS: BFViSTA significantly increased after surgery ( P  < .001). BFViICA and BFVBA significantly decreased after surgery (BFViICA P  = .005; BFVBA P  = .02). No significant difference was observed between BFVcICA before and after surgery. As a result, BFVtotal postoperatively increased by 6.8%; however, no significant difference was observed. Flow direction at M1 changed from antegrade to unclear after surgery in 5 patients. Intraoperative MCA pressure and MCA/RA pressure ratio significantly increased after surgery ( P  < .001). We found a stronger positive correlation between MCA pressure increase ratio and BFVtotal increase ratio in patients with lower pre-MCA pressure (r = 0.907, P  < .001). CONCLUSION: The visual and quantitative assessment of 4D flow MRI revealed that intracranial blood flow changes complementarily after STA-MCA bypass surgery. 4D flow MRI may detect the improvement of cerebral perfusion pressure.